1979
DOI: 10.1111/j.1464-410x.1979.tb04236.x
|View full text |Cite
|
Sign up to set email alerts
|

Diuresis Renography and Morphology in Upper Urinary Tract Obstruction

Abstract: The results of a combined study of 25 patients with idiopathic hydronephrosis are presented. Diuresis renography was performed pre-operatively and surgically removed specimens of the renal pelvis and ureter were examined by light and electron microscopy. There was good correlation between the results of these 2 methods of assessment which have defined 2 broad categories of patients with renal pelvic dilatation. These findings are discussed with particular reference to the clinical value of diuresis renography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…They furthermore found the predictive value of a posi tive test to be 92% while the corresponding value of a negative test was a little less (82%). A high sensitivity was also reported by Lupton et al [4], In 26 hydronephrotic kidneys they found a nonobstructed diuresis renogram to be correlated with normal renal pelvic mor phology at operation while obstruction at diuresis renog raphy was confirmed histopathologically in all cases. Other studies have also confirmed a high degree of accor dance between diuresis renography and renal pelvic pa thology [5].…”
Section: Discussionsupporting
confidence: 56%
“…They furthermore found the predictive value of a posi tive test to be 92% while the corresponding value of a negative test was a little less (82%). A high sensitivity was also reported by Lupton et al [4], In 26 hydronephrotic kidneys they found a nonobstructed diuresis renogram to be correlated with normal renal pelvic mor phology at operation while obstruction at diuresis renog raphy was confirmed histopathologically in all cases. Other studies have also confirmed a high degree of accor dance between diuresis renography and renal pelvic pa thology [5].…”
Section: Discussionsupporting
confidence: 56%
“…At about the same time, Whitaker introduced the antegrade pressure flow study [32] to diagnose obstruction. Studies comparing these two techniques were published in the following years, showing sometimes excellent and sometimes poor correlation [33][34][35][36][37][38]. Since then, the refinement of diuretic renography and new techniques such as ultrasonography and color Doppler studies limit the use of the Whitaker test to patients with extremely dilated upper urinary tracts in which renal function is poor and in selected cases in which the results of diuretic renography are equivocal or when nephrostomy tube is already in place [31].…”
Section: Diagnosis Of Obstructionmentioning
confidence: 99%
“…The interpretation of the underlying cause of Type Illb curves has been the source of some discussion. The moderate rate of washout which differentiates this diuretic response from the washout achieved in the Type Ilia curve has generally been classified as due to a partially obstructed collecting system (Lupton et al, 1979) although some workers have attributed it to a dilated collecting system (Britton & Maisey, 1983). The rate of clearance of activity from a reservoir will be proportional to the rate of flow through it, but inversely proportional to its volume.…”
mentioning
confidence: 98%